Application of SAW (Simple Additive Weighting) for the Selection of Campus Ambassadors - Iman Judi Tua Situmeang; Siti Hummairoh; Sonya Malinda Harahap; Mesran Mesran (STMIK Budi Darma, 2021)
Budi Darma University is one of the private colleges in North Sumatra, Indonesia. To make this campus even better, a campus ambassador was chosen who would later be assigned as student representatives to promote the campus to the community and also as an icon that could have a better impact on the campus environment. Campus ambassadors themselves are active students at the campus who are selected based on predetermined criteria according to the needs of the campus. In the process of selecting a campus ambassador to get more optimal results, a decision support system is needed. In this study using the simple additive weighting (SAW) method as decision support in selecting campus ambassadors.